Governance of Privacy Protection: How Laws Will Be Adopted to Address New Technologies? - Peilin Shi; Jenifer Sunrise Winter; Bin Zhang (International Telecommunications Society (ITS), 2021)
In accordance with UNCTAD data, out of 194 countries in the world, 132 countries have enacted laws to protect data and privacy. Among them, most of the laws were issued at the beginning of the 21st century. With the continuous development of digital technology, especially the widespread application of big data technology, existing legislation has been unable to deal with the privacy protection risks brought by new technologies. In recent years, Japan, South Korea, and other countries have begun to revise or expand the definition of personal information protection boundaries and content in laws and regulations to protect the personal information of their citizens in response to the development of new technologies. In early 2020, the COVID-19 epidemic suddenly broke out and quickly swept the world, posing unprecedented challenges to healthcare systems, lifestyles, economic development and social stability in countries around the world. Digital technologies and data applications have played an important role in COVID-19 detection and control, but their characteristics have also raised concerns about the security of personal data and privacy. How the law will be adjusted (or has been adjusted) to deal with new technology will be a challenge.This paper selects the countries (EU, the United States, Japan, South Korea, China) that have modified laws and regulations related to data security and privacy protection in recent years as research objects, analyzes their existing privacy protection laws and regulations governance framework, and then analyzes the privacy risks faced to the new technology. In particular, privacy regulations and compliance guidelines for the application of facial recognition, location tracking and distance learning technology during the COVID-19 epidemic. Then, the governance experience in dealing with the relationship between digital technology progress, personal information protection and public health in the special period was summarized. Finally, it summarizes the future development direction of privacy protection governance from the legal level.
Keywords: 330; Privacy Protection; New Technologies; Governance; COVID-19 epidemic